Let Us Debate! A Proposal to Promote Social Entrepreneurship in Physical Education Teacher Education - Capella-Peris, Carlos; Chiva-Bartoll, Óscar; Salvador-García, Celina; Maravé-Vivas, María (Journal of Teaching in Physical Education, 2023)
Purpose: To analyze the effects of debates on social entrepreneurship (SE) in physical education teacher education students (n = 38) from an urban university. Participants discussed the role that society, social class, gender, race, and violence play in sports. Method: A convergent parallel mixed-methods design with methodological triangulation was employed: QUAN + QUAL. Results: The quantitative results provide evidence regarding the positive effect of debates on SE. The qualitative analysis complements this outcome by describing how SE was developed, for example, facing a new teaching methodology, being challenged by peers and/or the teacher, analyzing different opinions and their implications, developing new arguments for discussion, discussing topics according to the students' interests, and leading the conversation while debating. Data transfor-mation and sentiment analyses provide supplemental information regarding the benefits provided. Discussion/Conclusion: Our results display how debates improve SE in physical education teacher education students, calling for new research in this direction.
Keywords: urban education; social effects; scalemixed-methods; JCR